2015
DOI: 10.1038/gim.2014.101
|View full text |Cite
|
Sign up to set email alerts
|

Primary-care providers’ perceived barriers to integration of genetics services: a systematic review of the literature

Abstract: Purpose: We aimed to systematically review the literature to identify primary-care providers' perceived barriers against provision of genetics services. Methods:We systematically searched PubMed and ERIC using key and Boolean term combinations for articles published from 2001 to 2012 that met inclusion/exclusion criteria. Specific barriers were identified and aggregated into categories based on topic similarity. These categories were then grouped into themes.Results: Of the 4,174 citations identified by the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
216
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(238 citation statements)
references
References 60 publications
11
216
0
Order By: Relevance
“…Similarly, a systematic review of research published from 2001-2012 concluded that a lack of knowledge and skills, along with attitudes and concerns about patient distress, were common barriers to PCPs integrating genetic services into patient management. 26 This past work confirms that PCPs' knowledge and attitudes are critical to their genetic testing utilization.…”
Section: Introductionsupporting
confidence: 54%
“…Similarly, a systematic review of research published from 2001-2012 concluded that a lack of knowledge and skills, along with attitudes and concerns about patient distress, were common barriers to PCPs integrating genetic services into patient management. 26 This past work confirms that PCPs' knowledge and attitudes are critical to their genetic testing utilization.…”
Section: Introductionsupporting
confidence: 54%
“…In personalized and precision medicine, provider knowledge and decision support have been identified as key issues to the integration of new genetic and genomic applications [20]. While some groups are developing EMR-based PGx CDS alerts [21,22] PGx consultation service staffed by a pharmacist and a physician geneticist [23].…”
mentioning
confidence: 99%
“…Medical geneticists then need to be cognizant of the PCMH, the patient/family, and their own specific role for each individual case. 8 While this answer may seem a little oversimplified, it truly is the best framework in which to establish the optimal working relationship for patients and their families. In discussions that we have had with PCPs and patients, the most common suggestion is improved communication.…”
Section: The Role Of the Medical Geneticist In The Pcmhmentioning
confidence: 99%